POS0644 IMPACT OF CHRONIC INFLAMMATION ON BODY COMPOSITION IN RHEUMATOID ARTHRITIS PATIENTS - Garcia Studer, A.; Ortiz-Márquez, F.; Borregón-Garrido, P.; Redondo-Rodriguez, R.; Manrique-Arija, S.; Mena-Vázquez, N. (Annals of the rheumatic diseases, 2024)
Background:Previous studies have described alterations in fat and lean mass in rheumatoid arthritis (RA) patients, but their relationship with inflammation remains unclear.Objectives:To analyze alterations in body composition in a cohort of RA patients with high accumulated inflammatory activity and to identify associated factors.Methods:We conducted a controlled cross-sectional observational study of a prospective cohort of RA patients. The cases were RA patients (ACR/EULAR 2010) with mean moderate-high inflammatory activity during the disease course who were selected to start first biologic treatment. The controls were subjects without inflammatory disease, matched for sex and age with cases. All patients were recruited consecutively from a rheumatology clinic. At the cutoff date, all patients were evaluated using a predefined questionnaire collecting clinical and analytical data, as well as body composition data through dual-energy X-ray absorptiometry (DXA). The main variables were lean mass and total fat mass (kg). Fat and lean mass of arms, legs, trunk, android, and gynoid (kg) were also assessed. The average inflammatory activity according to DAS28 and C-reactive protein (CRP) obtained at each visit since RA diagnosis was evaluated. Additional variables included comorbidities, anthropometric and clinical-analytical measurements, therapies, physical activity measured by the IPAQ questionnaire per Metabolic Equivalent of Task (METs), and adherence to the Mediterranean diet assessed by the validated MEDAS questionnaire. Statistical analysis included descriptive analysis, bivariate and two models of multivariate analysis.Results:A total of 140 subjects, 70 cases with RA, and 70 controls were included. Most of them were female (81.4%), with a mean (SD) age of 56.3 (11.8) years. Baseline characteristics of both patient groups are shown in Table 1. Patients with RA, compared to controls, presented a lower median (IQR) lean mass (kg) (37.2 [31.9-41.2] vs. 39.4 [36.1-44.0]; p=0.015) and a tendency towards a higher median (IQR) fat mass (kg) (28.3 [23.3-35.7] vs. 26.7 [19.2-44.0]; p=0.32). In patients with RA, fat mass showed a positive correlation with body mass index (BMI) (r=0.804; p<0.001), inflammatory parameters such as CRP (r=0.263; p=0.004) and ESR (r=0.224; p=0.017), and other analytical parameters such as triglycerides (r=0.327; p=0.001) and ACPA titers (r=0.336; p=0.008). Regarding lean mass, it also showed a positive correlation with BMI (r=0.265; p=0.038) and a negative correlation with ACPA titers (r=-0.182; p=0.048) and cholesterol levels (r=-0.224; p=0.014). In the multivariate analysis, factors independently associated with fat mass in patients with RA and high inflammatory activity were average DAS28-CRP (β= 0.243; p=0.015), average HAQ (β = -0.198; p=0.043), total cholesterol (β =0.167; p = 0.025), and BMI (β =0.817; p< 0.001). As for lean mass, independently associated factors were female gender (β = -0.732; p<0.001), age (β = -0.181; p=0.038), BMI (β = 0.336; p<0.001), and average CRP (β = -0.254; p=0.005).Conclusion:Patients with RA with high inflammatory activity and naive to biological therapy presented lower lean mass compared to controls. Clinical, inflammatory, and physical disability factors were associated with lower lean mass and higher fat mass in these patients.Table 1.Baseline characteristics of 70 RA patients and 70 controls.VariableRA N = 70Controls N = 70p-valueSex, female, n (%)57 (81.4)57 (81.4)1.000Age, years (DS)56.2 (12.3)56.4 (11.3)0.947Dislipidemia, n (%)16 (22.9)13 (18.6)0.532Arterial Hypertension, n (%)20 (28.6)18 (25.7)0.704Diabetes mellitus, n (%)8 (11.4)5 (7.1)0.382Smoker, n (%)18 (25.7)12 (17.1)0.037BMI, kg/m2, mean (SD)27.4 (4.4)26.9 (4.4)0.515Time since diagnosis of RA, months, median (IQR)126.4 (34.6 – 184.8)Rheumatoid factor >10U/ml, n (%)60 (85.7)0 (0.0)<0.001ACPA >20 U/ml, n (%)56 (80.0)0 (0.0)<0.001CRP, mg/L, median (IQR)9.4 (4.0-17.2)3.0 (2.0-4.0)<0.001DAS28-CRP, mean (DS)4.9 (1.15)DAS28-CRP average, mean (DS)3.7 (0.9)HAQ, mean (DS)1.4 (0.7)Synthetic DMARD, n (%)70 (100)Abbreviation; SD: standard deviation; IQR interquartile range.Acknowledgements:This work was supported by FIS Grant PI22/01207 (Instituto Carlos III, Fondos FEDER).Disclosure of Interests:None declared.